The Routledge companion to Christian ethics - Long, D. Stephen; Miles, Rebekah L. (Routledge religion companions, 2023)
"The Routledge Companion to Christian Ethics brings together two different but related disciplines; the first is contemplative or theoretical, asking what are the beliefs or doctrines that characterize Christianity, whilst the second is practical, asking what are the ethical practices that attend its teachings. The movement between the theoretical and practical aspects is not, however, one way, as doctrine and life are mutually informing. In this comprehensive volume, leading scholars address key topics, problems and debates in this hotly debated topic within a truly global context. Comprising over thirty-five chapters by a team of international contributors, the Handbook is divided into three parts based on the three persons of the Trinity: God the Father, God the Son, and God the Holy Spirit. Within these sections, cutting-edge issues are examined, including: God and genetics; War, peace and violence; White supremacy; Creation and sexuality; Digital ethics; Transgender studies; Climate change; Immigration and refugees. Adopting a practical approach that must consider new concerns that have arisen with recent social, political, and cultural shifts, The Routledge Companion to Christian Ethics is essential reading for students and researchers in Christian ethics, religious ethics and Christianity Studies. The Handbook will also be very useful for those in related fields, such as ethics and philosophy"--